Athletic Identification of Would-Be Specialists of Physical Education and Sports at the Institution of Higher Education - Diana Karanauskienė; Kęstutis Kardelis; Laimutė Kardelienė (Lithuanian Sports University, 2018)
Athletic identiﬁ cation indicates the level of person's identiﬁ cation with a role of an athlete. Different levels of sports identiﬁ cations are typical of all people: those who are sports professionals as well as those who only exercise. The students at the Lithuanian Academy of Physical Education (LAPE) are prepared to be sports coaches and teachers of physical education, and only some students choose the career of a professional athlete, so their identiﬁ cation with sports activities at the academy and their athletic identiﬁ cation might be rather different. The aim of the research was to reveal the manifestation of would-be physical education and sports specialists' athletic identiﬁ cation at the institution of higher education. The empirical research involved the triangulation of qualitative and quantitative methods. The questionnaire was used to determine the general tendencies of the research participants' athletic identiﬁ cation, and the interview was meant to establish its content and speciﬁ c features. The research results have important implications for the personnel of the institutions of higher education attemp- ting to facilitate student personal growth through participation in sports activities. The links of students' athletic identiﬁ cation with the variables in the higher school environment shows the presence of a pervasive athletic culture (Ferris et al., 2004) which results in the educational experience at the Academy. Athletic culture is experienced by students - athletes during their years of competitive, educational, and social development. Students - athletes' ﬁ rst contact with university environment is mediated through institutions - friends, coaches, practice and competitions. In some cases these factors increase athletes' satisfaction with collegiate experience and promote continued persistence toward a degree. Research results let us conclude that athletic identiﬁ cation at the institution of higher education is determined by students' activity in sports, their sports aspirations and plans, evaluations of sporting conditions at the higher school and perception of the importance of sports activities. Athletic culture at the institution of higher education is both the precondition and the outcome of students' favorable athletic identiﬁ cation. Research revealed the links between the manifestation of students' athletic identiﬁ cation and the following sociodemographic and other factors: gender, academic achievements and academic identiﬁ cation, sports aspirations, living place, professional identiﬁ cation, feelings and the evaluation of their higher school. Keywords: athletic identification, athletic culture, institution of higher education.